Pemanfaatan E-Government Berbasis Aplikasi Untuk Meningkatkan Kualitas Pelayanan Publikdi Kota Kendari - Wa Ode Sri Nani; Andi Syaiful Zainal; Darwan Sari (Program Studi Ilmu Pemerintahan, Universitas Muhammadiyah Kendari, 2021)
Application Integration Services of Kendari (LAIKA) is an e-government application that supports the performance of public services based on technology. This program has been operated in several offices in the city of Kendari. This study provides a general description of the quality of public services in the Kandai village sub –district office where has used the application system. Conducted in a descriptive qualitative manner. Data collection through observation, interviews, and document reviews. This study reveals that the quality of public services based on the LAIKA application has not been running well. The measurement of quality is based on three indicators, namely transparency, participation, and efficiency. In the aspect of transparency, there is no clarity of information related to public services. Meanwhile, in the aspect of public participation, it was found that community involvement was not optimal in utilizing this application. In reality, the hope of making public services accessible and easier has not yet been realized